2020
DOI: 10.1016/j.atmosenv.2020.117510
|View full text |Cite
|
Sign up to set email alerts
|

Ambient measurements of monoterpenes near Cannabis cultivation facilities in Denver, Colorado

Abstract: � Measurements near cannabis facilities increased background concentrations of monoterpenes by four times. � The types of monoterpenes that were measured varied widely across Denver, suggesting a diverse set of emission profiles. � Composition of measurements near emission sources were dominated by d-limonene, bmyrcene, and a-pinene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The same compounds are the dominant BVOCs in the grow room sampled by Knights, but the rank composition followed a different order: myrcene (68%), d -limonene (14%), α-pinene (13%), and β-pinene (5%). Due to the rarity of myrcene in cleaning and coating products, the author also proposed that it could be used as a sensitive tracer of cannabis operations, in agreement with Wang et al Furthermore, Knights observed a steady increase in concentrations of all compounds from months 3 to 4 and an abnormal peak of myrcene in the seventh month, indicating emissions rates are different due to growth stages or for different strains. BVOCs collected and analyzed from male and female plants of two cannabis species during the flowering stage showed the most abundant compounds to be β-myrcene, ( E )-β-ocimene, and terpinolene .…”
Section: Emissions From Cannabis Cultivationsupporting
confidence: 65%
See 3 more Smart Citations
“…The same compounds are the dominant BVOCs in the grow room sampled by Knights, but the rank composition followed a different order: myrcene (68%), d -limonene (14%), α-pinene (13%), and β-pinene (5%). Due to the rarity of myrcene in cleaning and coating products, the author also proposed that it could be used as a sensitive tracer of cannabis operations, in agreement with Wang et al Furthermore, Knights observed a steady increase in concentrations of all compounds from months 3 to 4 and an abnormal peak of myrcene in the seventh month, indicating emissions rates are different due to growth stages or for different strains. BVOCs collected and analyzed from male and female plants of two cannabis species during the flowering stage showed the most abundant compounds to be β-myrcene, ( E )-β-ocimene, and terpinolene .…”
Section: Emissions From Cannabis Cultivationsupporting
confidence: 65%
“…Initially, a literature search was conducted in December 2020 in Web of Science using the keywords “cannabis cultivation” and (“emissions” or “odor”), which returned few results. ,, Likewise, “hemp cultivation” and (“emissions” or “odor”) did not return studies of interest for this review. Given the difficulties encountered with the initial steps of a systematic review, the authors changed the approach.…”
Section: Review Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 a illustrates a chromatogram of the terpene extract from the floral tissue of cannabis. Among others, the major monoterpene components are limonene, β-myrcene, α-pinene, and linalool with traces of α-terpinolene and tran-ocimene [ 54 , 55 ] ( Figure 5 b), while predominate sesquiterpenes are E- caryophyllene, caryophyllene oxide, E -β-farnesene, and β-caryophyllene [ 56 ]. The cannabinoids are biologically synthesized from diterpene structures to form phenol terpenoids, which account for almost a quarter of all metabolites [ 26 ].…”
Section: Terpene Biosynthesis In Cannabismentioning
confidence: 99%